Community involvement and development: an inter-marriage of ISO 26000 and millennium development goals. Issue 9 (20th August 2014) - Katamba, David; Nkiko, Cedric Marvin; Kazooba, Charles Tushabomwe; Kemeza, Imelda; Mpisi, Sulayman Babiiha; Tyler, Colin
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose This research explores how ISO 26000 inter-marries with Millennium Development Goals (MDGs) with a view to demonstrate and recommend how businesses can successfully use this inter-marriage to solve society problems. Design/methodology/approach Case methodology was used to investigate how a company can use the social responsibility standard, ISO 26000, to guide its Corporate Social Responsibility (CSR) aimed at contributing to MDGs. We focused on the CSR dimension of community involvement and development [CI&D] interventions in health related MDGs [4, 5 and 6]. Data collection was by semi-structured interviews with CSR managers of the studied company, plus non-participant observation of CSR activities and projects. In order to develop a framework within which the collected data could be analyzed, we employed pattern-matching, explanation building, and time series analysis. For generalization purposes of findings, we were guided by the 'adaptive theory approach.' Findings The inter-marriage is much revealed in health and Wellness. This intermarriage also reveals cross cutting issues which support universal access to health care and prevent illnesses. Lastly, the inter-marriage is symbiotic in nature, that is, MDGs contribute what to achieve while ISO 26000 contributes how to achieve. Research limitations/implications The case study (Uganda Baati Ltd, - UBL) that informed this research is a subsidiary company of a multinational, SAFAL Group. This provided an indication that global or trans-national forces drive CSR/CI&D at UBL. Thus, our findings may not fit directly with a company that has a local/national focus of its CSR/CI&D. Practical implications We present guidelines to use and localize this intermarriage so as to focus CSR on global socio-economic development priorities, identify strategic stakeholders, and pathways to solutions for complex CI&D issues. Originality/value This research advances the Post-2015 MDG Development Agenda suggested during the United Nations MDG Summit in 2010 which called for academic contributions on how MDGs can be realized even after 2015.